Modern Corporate Finance, Investments and Taxation - Brusov, P (Springer, 2015)
This monograph is devoted to the modern theory of capital cost and capital structure and its application to the real economy. In particular, it presents a possible explanation to the causes of global financial crisis. The authors of the book modify the theory of Nobel Prize winners Modigliani and Miller to describe an alternative theory of capital cost and capital structure that can be applied to corporations with arbitrary lifetime and investment projects with arbitrary duration. The authors illustrate their theory with examples from corporate practice and develop investment models that can be applied by companies in their financial operations.